WATER DISPUTE IN CENTRAL ASIA: CONFLICT POTENTIAL - TRIPATHI, Anurag; GAUR, Punit (CENTRAL ASIA AND THE CAUCASUS, 2019)
The Central Asian republics (CARs), which emerged as independent states in the post-Soviet phase, faced several challenges. During the Soviet era, the CARs were agriculturally oriented towards the Soviet economy, and river water management was also centralized under the command economic model. However, with the collapse of the Soviet Union, the CARs had to review the existing water management arrangements. This is where the absence of a Moscow-centric central authority has proven detrimental to the region endowed with two major rivers and their several subsidiaries. In this context, the paper suggests an emphasis on multilateralism, rather than bilateralism, as a more feasible approach to river water management. Clearly, multilateralism would promote a more equitable solution compared to bilateralism, which does not adopt a holistic approach to the region. Considering the fact that the region is characterized by a water crisis in addition to the fragility of the environment makes a multilateral arrangement significantly more appropriate for the region in the long term.